2000
DOI: 10.1152/ajpregu.2000.278.6.r1474
|View full text |Cite
|
Sign up to set email alerts
|

Central oxytocin modulates exercise-induced tachycardia

Abstract: We have shown that vasopressinergic projections to dorsal brain stem are activated during exercise and facilitate exercise tachycardia in both trained (T) and sedentary (S) rats (Dufloth DL, Morris M, and Michelini LC. Am J Physiol Regulatory Integrative Comp Physiol 273: R1271-R1282, 1997). In the present study, we investigated whether oxytocinergic projections to the nucleus of the solitary tract (NTS)-dorsal motor nucleus of the vagus (DMV) complex (NTS/DMV) are involved in the differential heart rate (HR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
105
1
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(136 citation statements)
references
References 38 publications
18
105
1
12
Order By: Relevance
“…2,3,5,12,14 In brief, a catheter was placed in the femoral artery and exteriorized on the back of the neck under anesthesia. After a 24-hour recovery period, the catheter was connected to the recording system, and the rat was allowed to rest for stabilization of cardiovascular parameters; basal values of arterial pressure (AP) and heart rate (HR) were then recorded in conscious, freely moving rats for Ϸ30 minutes.…”
Section: Functional Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5,12,14 In brief, a catheter was placed in the femoral artery and exteriorized on the back of the neck under anesthesia. After a 24-hour recovery period, the catheter was connected to the recording system, and the rat was allowed to rest for stabilization of cardiovascular parameters; basal values of arterial pressure (AP) and heart rate (HR) were then recorded in conscious, freely moving rats for Ϸ30 minutes.…”
Section: Functional Measurementsmentioning
confidence: 99%
“…For example, whereas vasopressin resets baroreceptor reflex control of the heart toward higher heart rate values and improves exercise tachycardia, 12,13 OT improves reflex bradycardia and blunts exercise tachycardia. 14,15 Furthermore, we showed that vasopressinergic and oxytocinergic modulation of cardiovascular control in normotensive rats is improved after training, resulting in occlusion of reflex bradycardia and thus facilitating tachycardic response and increased cardiac output during dynamic exercise. 13,16,17 There is no information, however, on the efficiency of vasopressin and OT modulation of cardiovascular control in hypertensive subjects.…”
mentioning
confidence: 93%
“…Para o treinamento, foi utilizado protocolo de treinamento anteriormente padronizado (DUFLOTH et al, 1997;BRAGA et al, 2000), realizado 5 vezes/semana, 1h/dia por 1, 2, 4, 8 ou 12 semanas, sempre com 0% de inclinação.…”
Section: Grupos Experimentaisunclassified
“…• a administração de VP no NTS não alterou a sensibilidade do reflexo, mas diminuiu a resposta bradicárdica por reduzir a inibição simpática durante elevações transitórias da PA, deslocando o ponto de operação do reflexo para níveis mais elevados de FC (MICHELINI, 1994(MICHELINI, , 1998BONAGAMBA, 1988) • em ratos sedentários e treinados observou-se durante exercício dinâmico aumento do • pré-tratamento do NTS com antagonista de receptores de OT (OTR) não alterou a resposta pressora, mas potencializou a taquicardia do exercício apenas nos ratos treinados, sugerindo que o treinamento ativa mecanismos OTérgicos supra-bulbares de controle da FC os quais, determinam redução da taquicardia do exercício; nenhuma alteração de PA ou FC após bloqueio dos OTR foi observada em ratos sedentários submetidos ao exercício dinâmico (BRAGA et al, 2000;MICHELINI, 2001);…”
Section: Introdução/justificativaunclassified
“…• tanto nos grupos treinados quanto sedentários, a administração exógena de OT no NTS determinou redução significativa e similar da taquicardia do exercício, sugerindo que o treinamento não alterava receptores, mas apenas a disponibilidade do neurotransmissor, aumentada após treinamento (BRAGA et al, 2000;MICHELINI, 2001);…”
Section: Introdução/justificativaunclassified